Las corrientes en chorro sobre el Atlántico norte en el invierno 2009-2010 - Sánchez-Laulhé Ollero, José María (Revista Tiempo y Clima, 2017)
Ball, S. ,2011: Exceptional rainfall in Gibraltar during winter 2009/2010. Weather, 66: 22–25. doi:10.1002/wea.733, Barnes, E. A., y D. L. Hartmann. 2010. Influence of eddy-driven jet latitude on North Atlantic jet persistence and blocking frequency in CMIP3 integrations, Geophys. Res. Lett., 37, L23802, doi:10.1029/2010GL 045700. Christenson, C.E., J.E. Martin, y Z.J. Handlos, 2017: A Synoptic Climatology of Northern Hemisphere, Cold Season Polar and Subtropical Jet Superposition Events. J. Climate, 30, 7231–7246, https://doi.org/10.1175/JCLI -D-16-0565.1 Handlos, Z.J. y J.E. Martin, 2016: Composite Analysis of Large-Scale Environments Conducive to Western Pacific Polar/Subtropical Jet Superposition. J. Climate, 29, 7145–7165, https://doi.org/10.1175/JCLI -D-16-0044.1 Lee, S. y H. Kim, 2003: The Dynamical Relationship between Subtropical and Eddy-Driven Jets. J. Atmos. Sci., 60, 1490–1503, https://doi.org/10.1175/1520-0469(2003)060<1490:TDRBSA >2.0.CO ;2 Lindzen, R. S., y A. Y. Hou, 1988: Hadley circulations for zonally averaged heating centered off the equator. J. Atmos. Sci., 45, 2416–2427, doi:https://doi.org/10.1175/1520. Lorenz, D. J., 2014b: Understanding midlatitude jet variability and change using Rossby wave chromatography: Wave–mean flow interaction. J. Atmos. Sci., 71, 3684–3705, doi:https://doi.org/10.1175/JAS -D-13-0201.1. O’Rourke, A., y G. K. Vallis, 2013: Jet interaction and the influence of a minimum phase speed bound on the propagation of eddies. J. Atmos. Sci., 70, 2614–2628, doi:https://doi.org/10.1175/JAS - D-12-0303.1. Polvani, L. M., y P. J. Kushner, 2002: Tropospheric response to stratospheric perturbations in a relatively simple general circulation model. Geophys. Res. Lett., 29, 18-1–18-4, doi:https://doi.org/10.1029/2001GL 014284. Son, S. W., y S. Lee, 2005: The response of westerly jets to termal driving in a primitive equation model. J. Atmos. Sci., 62, 3741-3757, doi:https://doi.org/10.1175/JAS 3571.1 Sprenger, M., G. Fragkoulidis, H. Binder, M. Croci-Maspoli, P. Graf, C.M. Grams, P. Knippertz, E. Madonna, S. Schemm, B. Škerlak, y H. Wernli, 2017: Global Climatologies of Eulerian and Lagrangian Flow Features based on ERA -Interim. Bull. Amer. Meteor. Soc., 98, 1739–1748, https://doi.org/10.1175/BA MS-D-15-00299